(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Video steganography is the art of information hiding mechanism using multimedia. The purpose of the multimedia is getting enlarged day by day. Face recognition systems are also very useful in many applications such as monitoring system, biometrics and security. Steganography is an art work to conceal the data into a multimedia file. The purpose of using a multimedia file after than any other file is to accommodate a huge amount of information. The experimental results for different images also show good performance. In this thesis, a new face recognition system using the Independent Component Analysis Signcryption Algorithm (ICASA) within video steganography is proposed.